Blends of sulfonated polysulfone/polysulfone/4, 4′‐diaminodiphenyl methane‐based benzoxazine: multiphase structures and properties. Issue 1 (24th June 2014) - Xia, Yiqing; Yang, Po; Miao, Yu; Zhang, Chaoliang; Gu, Yi
<x xml:space="preserve">Abstract</x> The curing‐temperature of BZ‐m was lowered with the addition of SPSU. More important is the toughness of PBZ‐m greatly improved after modified with SPSU and PSU through forming complicated multiphase structures. <boxed-text content-type="graphic" id="pi4766-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>